Multi-scale modeling of metal-CNT interfaces - Claus, M.; Fediai, A.; Mothes, S.; Pacheco, A.; Ryndyk, D.; Blawid, S.; Cuniberti, Gianaurelio (Giovanni); Schroter, M. (18th International Workshop on Computational Electronics, IWCE 2015, 2015)
It is well known that the metal-CNT interfaces in CNTFETs have been a key factor limiting the device performance. Efforts have been made to improve the understanding of physics at these interfaces and the contact length scaling behavior seen in experiments [1]. However, the related interface phenomena are not fully understood [1], which makes it difficult to improve the device performance. Typically, the impact of the metal- CNT interfaces on the device characteristics is lumped into a resistance which is commonly labeled as the contact resistance Rc (including the contribution of both, the source and the drain contact). While for digital applications the contact length is an critical parameter in terms of overall device size, for analog HF applications as described in [2] the contact dimensions are relaxed which allows an investigation of the metal-CNT interfaces in the long-contact-limit. As suggested in [3], a detailed understanding of the contact physics is mandatory for optimizing the device linearity of CNTFETs.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CNTFETs; Computational modeling; Contact resistance; Effective mass; Integrated circuit modeling; Metals